Effect of Work Conflict on Employees Job Satisfaction: The Case of College of Distance Education, University of Cape Coast - Moses Segbenya; Fred Peniana; Ebenezer Aggrey (European Scientific Journal, ESJ, 2018)
The purpose of the study was to examine the effects of work life balance on employees’ job satisfaction at College of Distance Education, University of Cape Coast, Ghana-Africa. The study adopted the quantitative research approach specifically a correlational design. From populations of 242, a sample of 140 teaching and non teaching staff of the College was drawn across three spectrums of staff using simple random sampling technique. Instrument for data collection was questionnaire which had items measured on a scale of 1 to 4 with 1 representing strongly disagreement while 4 represented strong agreement. It was found that there was high level of conflict between work schedules and other social demands (low rating for work life balance) among staff of the College. Additionally, the level of job satisfaction among CoDE staff was low. It was also found that that there was a negative but moderate and significant relationship between work life conflict and job satisfaction among staff of CoDE. It was therefore recommended that management of CoDE should: introduce leave schedule or a day off for staff in order to have sufficient time to attend to their personal, marital and social life and rest; introduce job rotation to ensure job satisfaction and work life balance and also introduce inter-unit assignment and recreational activities for staff on public holidays.